Serum Ghrelin and Glucagon-like Peptide 1 Levels in Children with Prader-Willi and Bardet-Biedl Syndromes - Doğa Türkkahraman; Suat Tekin; Merve Güllü; Güzin Aykal (Galenos Yayincilik, 2024)
INTRODUCTION: Prader-Willi syndrome (PWS) and Bardet-Biedl syndrome (BBS) are causes of pediatric syndromic obesity. We aimed to investigate a possible role for ghrelin and glucagon-like peptide-1 (GLP-1) in the pathophysiology of PWS and BBS. METHODS: The study included 12 children with PWS, 12 children with BBS, 13 pediatric obese controls (OC) and 12 pediatric lean controls (LC). Fasting serum ghrelin and GLP-1 levels were measured by ELISA. RESULTS: In the PWS group, no significant difference was detected for median ghrelin levels when compared with OC and LC, which were 0.96 (0.69-1.15), 0.92 (0.72-1.20) and 1.13 (0.84-1.29) ng/mL, respectively. Similarly, there was no difference in PWS median GLP-1 levels when compared with OC and LC; 1.86 (1.5-2.94), 2.24 (1.62-2.78) and 2.06 (1.8-3.41) ng/mL, respectively. In the BBS group, there was no difference in median ghrelin levels when compared with OC and LC; 1.05 (0.87-1.51), 0.92 (0.72-1.20) and 1.13 (0.84-1.29) ng/mL, respectively. Neither was there a significant difference in median GLP-1 levels; 2.46 (1.91-4.17), 2.24 (1.62-2.78) and 2.06 (1.8-3.41) ng/mL for BBS, OC and LC, respectively. DISCUSSION AND CONCLUSION: There were no differences in median fasting ghrelin or GLP-1 levels when comparing patients with PWS and BBS with obese or lean peers. However, similar studies with larger series are needed.